Susceptibility of multidrug resistant clinical pathogens to a chlorhexidine formulation - Günther, Frank; Kaiser, Stefan J.; Fries, Tamara; Frank, Uwe; Mutters, Nico T. (Journal of preventive medicine and hygiene, 2015)
Multidrug resistant pathogens are a widespread problem in the hospital setting especially on intensive care units (ICU). This study evaluated the susceptibility of clinical isolates of gram-negative extensively drug resistant (XDR) organisms, methicillin-resistant Staphylococcus aureus (MRSA), and vancomycin-resistant Enterococcus (VRE) to a proprietary chlorhexidine digluconate (CHG) formulation used in one brand of CHG-impregnated cloths. Ten isolates each of XDR Pseudomonas aeruginosa, XDR Acinetobacter baumannii, XDR Klebsiella pneumoniae, XDR Escherichia coli, MRSA, and vancomycin-resistant Enterococcus faecium from our hospital were tested. All isolates were susceptible to the proprietary CHG formulation (0.5%, 1%, 2%), with 99% to 100% suppression of growth at the earliest time point in time kill assays (1 minute for gram-positive and 15 seconds for gram-negative organisms). Minimum inhibitory concentrations ranged from 1:4096 to 1:65536 for MRSA, 1:1024 to 1:2048 for VRE, 1:2048 to 1:4096 for XDR .E. coli, 1:512 to 1:2048 for XDR A. baumannii, 1:512 to 1:1024 for XDR P. aeruginosa, and 1:512 to 1:1024 for XDR K. pneumoniae. Cloths impregnated with this CHG formulation provide effective protection against colonization and infection by many pathogens. This study provides in vitro evidence that the proprietary CHG formulation used in one brand of CHG-impregnated cloths is effective against XDR gram-negative organisms, MRSA, and VRE.
Gesehen am 02.02.2021